Identifying Permanently Disabled Workers with Disproportionate Earnings Losses for Supplemental Payments - Seabury, Seth A. (RAND Corporation, 2014)
In September 2012, California adopted legislation that includes a program to provide supplemental payments to injured workers whose permanent disability benefits are disproportionately low compared to their earnings loss. This report makes recommendations about the implementation of this program.